Effect of impact damage on fatigue performance of structures reinforced with GLARE bonded crack retarders. (November 2015) - Syed, Abdul Khadar; Fitzpatrick, Michael E.; Moffatt, James E.; Doucet, Jeremy; Durazo-Cardenas, Isidro
Highlights: Thermal residual stresses owing to bonding GLARE bonded crack retarders are low. Impact damage at 30 J or above resulted in visible plastic deformation on GLARE. Impact damage depth is proportional to impact energy. Application of bonded crack retarder resulted in improved fatigue performance. Specimens with impact damage showed lower fatigue life than undamaged specimens. Abstract: Fibre-Metal Laminates (FML) such as GLARE are of interest as bonded crack retarders (BCR) to improve the fatigue performance of aircraft structures. The degradation of the performance of the crack retarder in service if subjected to damage is a critical factor in designing with this concept. Bonded assemblies of an aluminium alloy substrate reinforced with a GLARE strap were prepared, and were subjected to low velocity impact damage onto the GLARE, with impact energies ranging from 10 to 60 J. The thermal residual stresses developed during the bonding process of the GLARE to the aluminium were determined using neutron diffraction, and the change in the thermal residual stresses owing to impact damage onto the GLARE was evaluated. Pre- and post-impact fatigue performance of the BCR assemblies has been investigated. The results show that the BCR provides an improvement in fatigue life, but the reduction is impaired following impact damage. The results show that monitoring of impact damage will be critical in the damage tolerance assurance for aerospace structures containing bonded crack retarders.